PENGARUH PROMOSI, KUALITAS PRODUK DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SEPEDA MOTOR YAMAHA MIO (STUDI KASUS PADA KONSUMEN DEALER SUMBER BARU MOTOR MUNTILAN) - Kholifah, Nur; Waluyo, Handoyo Djoko; Nurseto, Sendhang (Jurnal Ilmu Administrasi Bisnis, 2014)
This study aims to determine the effect of promotion, product quality, and product’s design to the purchasing decision on Yamaha Mio at Sumber Baru Motor Dealer Muntilan. The population of this study are the consumers who purchased Yamaha Mio motorcycles. The samples of this study were 96 respondents that taken by purposive sampling. The data collection technique is done by using a questionnaire. This thesis measurement scale was using Likert scale. The data analysis was simple linear regression and multiple regression. The promotion variables influence the purchasing decisions at 78.3 percent. The quality of the product variables affects the purchase decisions at 51.5 percent. The product design variables influence the purchasing decisions at 81.6 percent. The promotion variable, product quality, and product design influenced to the buying decision for 85.9 percent. This means that the increasing of the promotion, the product quality, and the product design is expected to increase the purchasing decision. Based on this research, Sumber Baru Motor Dealer Muntilan trying to create exciting promotions and improve the quality of the product as well as the product’s design of Yamaha Mio motorcycle which believed has a positive impact on purchasing decisions.